New technologies and possibilities of breast cancer staging by the criterion N ex vivo - Sh. Kh. Gantsev; M. G. Galeyev; R. Sh. Ishmuratova; D. S. Tursumetov; V. Yu. Tikhonova; A. V. Sultanbayev; Sh. M. Khusnutdinov; M. A. Tatunov; F. Sh. Zainullin (Опухоли женской репродуктивной системы, 2014)
The study was undertaken to improve breast cancer (BC) staging by the criterion N ex vivo, by applying the up-to-date ultrasound and microsurgical technologies. A LySonix 3000® with PulseSelectTM system was used to expose lymph nodes and vessels. Axillary adipose tissue classically exposed was examined in 70 patients with Stages II-III BC. Lymph vessels and nodes were separated by the sonolipodestruction technique. The findings permit sonolipodestruction to be used for ex vivo total lymph dissection for BC as a method that improves its N-staging. Sonolymphodissection opens up fresh opportunities for studying the anatomic structure of the lymphatic apparatus.